Sentient Futures: The Hydra Trilogy by Future Cities Lab. (July 2015) - Gattegno, Nataly; Johnson, Jason Kelly; Luebkeman, Chris
<x xml:space="preserve">Abstract</x> Nataly Gattegno and Jason Kelly Johnson, the founding principals of San Francisco‐based Future Cities Lab, conjure up a vision of the parched, forever thirsty California of 2050, beset by water scarcity and the extinction of its natural species.